THE EFFECT OF USING DAILY CONVERSATION YOUTUBE VIDEO TOWARDS STUDENT SPEAKING SKILL AT THE ELEVENTH GRADE STUDENT OF SMAN 1 CIHARA, LEBAK BANTEN IN ACADEMIC YEAR 2021/2022 - wini, wini nuraini; Sudirman, Ade; Gumelar, Rizdki Elang (EDUCATE, 2024)
Wini Nuraini (2022). “The effect of using daily conversation YouTube video towards student speaking skill at the eleventh grade student of SMAN 1 Cihara, Leabak Banten, Academic Year 2021/2022”. This research paper aims to determine the significant effect of daily conversation YouTube videos on speaking skill of Class Xl SMAN 1 students Cihara Lebak-Banten Academic Year 2021/2022. Research Paper using a quantitative approach. This research is conducted from October to November, and researcher have chosen two classes, namely experimental class and control class. The technique in selecting the sample is take random cluster sampling; And analyzing the data, the researcher used Paired sample test with SPSS 22 statistics to analyze the hypothesis test. Researcher have found t-count results (-5.971) and Significant = 0.000 <0.05. From this the data can be interpreted that there is a significant difference between the two group in obtaining a score, because the result is a significance value of less than 0.05 which means Ha is accepted. Therefore, the researcher concludes that. The application of daily conversation YouTube videos has a good effect on students' speaking skills. Keywords: daily conversation, YouTube video, speaking skill.